Identification of Moves Structure in the Discussion Section of Social Sciences Doctoral Research Thesis - Urooj Fatima Alvi; Dr. Muhammad Asim Mehmood; Dr. Shafqat Rasool (Linguistics and Literature Review, 2017)
This study describes the move structure of sub-genre; the discussion part in the doctoral theses of Pakistani research scholars. The study embraces six disciplines of social sciences, i.e. Education, Economics, Geography, Sociology, Statistics and Psychology. Thirty doctoral theses have been retrieved from Higher Education Commission (HEC) Pakistan Research Repository. Total data consist of 18, 80, 566 words approximately. The textual data of the discussion part of doctoral research thesis are analyzed in terms of the analysis of Peacock (2002) model which is the modified version of Dudley Evans (1994) move analysis. It is quite similar to Dudley’s model, but in addition to the 9 moves, move cycle is also proposed by Peacock. Not even a single obligatory move is found in selected theses which reveal that the rhetorical pattern of Pakistani PhD scholars does not match with this model of move structure. Contrary to move structure, move cycles proposed by Peacock (2002) are largely established in those research thesis. This study may be beneficial for PhD supervisors and research scholars to construct the relevant part with proper move structure for effective writing.